Enhancing Pre-Numeracy Readiness of Preschool Children - Chandra, Reetu (THE PRIMARY TEACHER, 2022)
In the process of acquiring new information, cognitive skills help children think critically and creatively thus, solving problems. Preschool is the right place to begin by providing such input to young children. These inputs are vital to the development of pre-numeracy competencies called pre-numeracy readiness among preschool children, necessary for improving learning outcomes in mathematics in schools. These also help increase children’s participation in school, strengthen retention, and thus ensure success in school. Realising the significant role of pre-numeracy in preschool children for their future learning and development, a study was conducted in preschools of four Municipal Corporation of Delhi (MCD) schools. This study intended to find out the existence of pre-numeracy competencies in the curriculum and among children. For this purpose, curriculum content analysis, classroom observation, and assessment of the level of pre-numeracy competencies among 82 preschool children were done to identify the learning gaps. To address the identified gaps, a set of activities were suggested to be included in the curriculum. The data was collected by the use of an observation schedule, a checklist to review curriculum content, and a school readiness instrument. The classroom observation suggested that though the curriculum contained some of the pre-numeracy activities in practice, such activities were rarely conducted. Gap analysis suggested that the majority of children were weak in the field of relative comparison: number-greater/lesser followed by making different patterns using different shapes, understanding pre-number concepts, identifying sequence and describing in words and understanding the concept of space. This study has the potential to identify the gaps in pre-numeracy readiness among preschoolers and provide possible solutions to address these issues at a large scale.